EFEKTIVITAS PROGAM KELURAHAN TANGGUH BENCANA OLEH BPBD KOTA PADANG - Hana Salsabila; Zikri Alhadi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
The background of this research is to examine the effectiveness of the occurrence of several problems in the Tangguh Kelurahan Disaster Program by BPBD Kota Padang which can be seen in the parameters of the Study in Padang City which aims to determine the Effectiveness of the Tangguh Kelurahan Disaster Program by BPBD Kota Padang. This research is a qualitative research with a descriptive approach using source triangulation method. The results of the study showed that the Effectiveness of the Tangguh Disaster Village Program by BPBD Kota Padang concluded that the program aimed at Kelurahan Olo was right on target, but the socialization was not maximized and there were still many factors that influenced the effectiveness of the Kelurahan Tangguh Disaster Program by BPBD Kota Padang.